Effect of ultrasound-microbubble exposure on acute myeloid leukemia cancer cell proteome - Joelle Stilwell; Daron A. Savaya; Emmanuel Sakarya; Charlotte Ferworn; Eleanor Cloves; Roberto J. Botelho; Costin N. Antonescu; Raffi Karshafian (Scientific Reports)
Abstract The application of ultrasound in combination with microbubbles (USMB) induces a broad spectrum of bioeffects on cells including plasma membrane disruption, cytoskeleton rearrangement, influx/efflux of cytosolic/extracellular molecules, metabolic stress and signalling pathways. This study investigated the effect of USMB on cell proteomics in human acute myeloid leukemia cells. Cells (OCI-AML-5) in suspension were exposed to ultrasound (f = 1 MHz, PD = 20 μs and PRP = 1 ms for 120 s) with and without microbubbles (Definity at 1.7% v/v) at varying acoustic pressures. Following exposure, cells were analysed using flow cytometry, mass spectrometry and immunoblotting. USMB enhanced cell membrane permeability (~ 37%), as expected, and induced significant changes in the cell proteome. Of 6825 proteins, 78 (~ 1.14%) were statistically significant and had a fold-change (≤ 0.8 or ≥ 1.2) compared to untreated control, referred to as a differentially expressed protein (DEP). The highest fold change of ~ 4–5 was induced in HMOX1 protein. The protein expression depended on acoustic pressure, presence of microbubbles and elapsed-time following exposure to ultrasound. Western blotting analysis confirmed the effect of USMB on three proteins (HMOX1, BACH1 and ANXA1) with R2 values > 0.9. In addition, the gene ontology analysis based on DAVID bioinformatics indicated that the DEPs are associated with GO cellular components such as plasma membrane and exosomes, which can be affected by USMB. This study suggests that targeted changes in the cell proteome may be induced with USMB to potentially optimize existing therapies and develop new cancer therapeutic targets.